Removal of Nickel (ii) using modified spent mushroom waste of pleurotus ostreatus / Aini Syahirah Abd Ghani - Abd Ghani, Aini Syahirah (2015)
This study investigates CaCO>3 modified spent mushroom waste of Pleurotus ostreatus biosorbent has the potential as environmetal friendly and cost-effective biosorbent for the biosorption of nickel (II) from aqueous solution. The effect of parameters of biosorbent weight, initial pH, contact time, initial nickel (II) concentration and temperature were carried out. The physical and chemical properties of the biosorbent were investigated by analytical method of SEM/EDX, FTIR and pHpzc analysis. At 50 % removal from 50 mg/L of nickel (II) concentration, 0.09 g biosorbent weight was determined. The optimum initial pH and contact time were at unadjusted pH 5.0 and 30 minutes, respectively. The characterization by SEM analysis showed the 'muddy-like' smooth surface was formed after the biosorption due to the nickel (II) deposited on the modified biosorbent surface. From FTIR analysis, hydroxyl, carboxylic acid and ester functional groups were involved in this biosorption study. In addition, pH 7.5 was identified as point of zero charge for CaC03 modified spent mushroom waste of Pleurotus ostreatus biosorbent in pHpzc analysis. In this study, it concludes that CaCOs modified spent mushroom waste of Pleurotus ostreatus is an effective and low cost biosorbent for nickel (II) removal from aqueous solution, especially in low concentration wastewater.